Poliuretanos obtidos de fonte renovável para aplicação em produtos capilares - Oliveira, Elisângela Aparecida Scorsato (Universidade Federal de São Carlos, 2015)
One of the most remarkable and diverse physical characteristics among human beings - and, thus, fundamental for personal identity - is hair. The search for personal hair care products has been increasing in the last years and Brazil is the third largest consumer market for these products. There is a constant quest for cosmetic products able to align, relax and treat hair fibers. There are some products for this purpose, such as smart brushes, Japanese brushes and definitive brushes, among others. In this context, the aim of this project was to synthesize and characterize polyurethane obtained from a renewable source as well as evaluate its effectiveness as a hair treatment agent. Therefore, scanning electron microscopy (SEM), atomic force microscopy (AFM), Fourier-transform infrared spectroscopy (FTIR), nearinfrared reflectance spectroscopy (NIRS) and mechanical tests for tensile properties were used. The FTIR results confirmed the synthesis of the polyurethane. The polymer was associated with citric acid, glycolic acid, lactic acid, and sodium hydroxide with glycose, in order to increase adhesion of the polymer onto the hair fiber. After application, better hair fiber alignment and increased hair roughness were noticed. Through the spectroscopic analysis it was established that a chemical interaction between the polymer, its associations and hair was present. The micrographs also suggested that there was a deposition of the polymer on the hair fibers. The results indicated that the polyurethane and their associations with citric acid and sodium hydroxide with glycose, are promising for applications in hair care products.
Polyurethanes source of renewable obtained for use in hair care products
Keywords: Cabelo; Hair; Poliuretanas; Polyurethanes; Mamona; Castor beans; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA